The Influence of the Audit Committee and Corporate Social Responsibility Disclosure on Earnings Management - Aprilia Pasca Ratiningsih; Yeterina Widi Nugrahanti (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to see the effect of Audit and Disclosure of Corporate Social Responsibility (CSR) on Earnings Management. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The total population in this study is 128 companies listed on the Indonesia Stock Exchange (IDX). The sample taken is a company engaged in the manufacturing sector on the Indonesia Stock Exchange (IDX) which was selected using a purposive sampling method. The analytical method used in this research is quantitative analysis. The results of the study simultaneously show that the Frequency of Audit Committee Meetings and Disclosure of Corporate Social Responsibility (CSR) have a negative influence on Earnings Management.